The Video-Sound Correlation in the “Play Has No Limits” Advertising Campaign: A Semiotic Perspective - Butkutė, Vitalija; Urbanavičiūtė-Globienė, Asta (Vilnius University Open Series, 2025)
With the internet becoming ingrained in everyday life, it has transformed into not just a source of entertainment but also a daily tool. As businesses began establishing their presence online, internet advertising quickly spread, and its volume grew so large that companies had to start searching for new ways to capture public attention. As a result, advertisements became increasingly unique, creative, and colorful. Since the goal of advertising shifted beyond merely selling, its value also began to increase. However, the growing complexity of advertising raises the question whether the advertisement effectively engages the audience, and if the message it conveys truly aligns with what the company wants to communicate, and how the audience responds to this ever more intriguing way of promoting both the brand and its product. To answer these questions, it is essential to understand how the constantly exposed audience interprets the information being conveyed to them, specifically, what deeper meaning(s) they perceive in the advertisements. This deeper meaning, which can be seen as a collection of signs, is part of the science of semiotics. By using semiotics, we can take a closer look not only at the signs themselves but also at the system of signs which consists of sensory levels, systems of signification, and spatiality.